2018
DOI: 10.1097/ijg.0000000000000826
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Eye Shield Reduces Limbal Strain and Its Variability During Simulated Sleep in Adults With Glaucoma

Abstract: Wearing a mask reduced limbal strain and variation in limbal strain during simulated FD sleep, particularly in eyes with past field worsening, as did some facial features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Additionally, we showed that wearing protective eye gear prevents this large external pressure‐induced IOP increase, a finding confirmed by a similar effect described wearing a customized protective mask (Flatau et al. ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, we showed that wearing protective eye gear prevents this large external pressure‐induced IOP increase, a finding confirmed by a similar effect described wearing a customized protective mask (Flatau et al. ).…”
Section: Discussionsupporting
confidence: 84%
“…found similar results of an increased IOP caused by pressure of a pillow, which were abolished by wearing a customized protective mask (Flatau et al. , ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation